2004
DOI: 10.1136/gut.2003.027540
|View full text |Cite
|
Sign up to set email alerts
|

Arginine stimulates intestinal cell migration through a focal adhesion kinase dependent mechanism

Abstract: Background: L-Arginine is a nutritional supplement that may be useful for promoting intestinal repair. Arginine is metabolised by the oxidative deiminase pathway to form nitric oxide (NO) and by the arginase pathway to yield ornithine and polyamines. Aims: To determine if arginine stimulates restitution via activation of NO synthesis and/or polyamine synthesis. Methods: We determined the effects of arginine on cultured intestinal cell migration, NO production, polyamine levels, and activation of focal adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 49 publications
1
80
0
2
Order By: Relevance
“…В экспериментах с эндотелиальными клетками линии TR-ВВВ индуцированная под влиянием провоспалитель-ных цитокинов iNOS-зависимая продукция NO полностью ингибировалась после воздействия АД и полностью восстанавливалась при добавле-нии в культуральную среду экзогенного аргинина [5]. Показано, что миграция клеток эпителия ки-шечника связана с аргинин-зависимой продук-цией клетками NO, активностью FAK -киназы фокальных контактов [17] и киназой pp70s6k -ключевым регулятором 5' -концевой олигопи-римидин mRNA трансляции [18]. Полиамины синтезируются во всех типах клеток и участвуют в процессах транскрипции, трансляции и репли-кации [6].…”
Section: т 19 №unclassified
See 1 more Smart Citation
“…В экспериментах с эндотелиальными клетками линии TR-ВВВ индуцированная под влиянием провоспалитель-ных цитокинов iNOS-зависимая продукция NO полностью ингибировалась после воздействия АД и полностью восстанавливалась при добавле-нии в культуральную среду экзогенного аргинина [5]. Показано, что миграция клеток эпителия ки-шечника связана с аргинин-зависимой продук-цией клетками NO, активностью FAK -киназы фокальных контактов [17] и киназой pp70s6k -ключевым регулятором 5' -концевой олигопи-римидин mRNA трансляции [18]. Полиамины синтезируются во всех типах клеток и участвуют в процессах транскрипции, трансляции и репли-кации [6].…”
Section: т 19 №unclassified
“…Полиамины синтезируются во всех типах клеток и участвуют в процессах транскрипции, трансляции и репли-кации [6]. От синтеза полиаминов зависит мигра-ция клеток кишечного эпителия [17], а снижение уровня синтеза полиаминов подавляет формиро-вание ламеллиподий и стресс-волокон в мигри-рующих клетках [13,21].…”
Section: т 19 №unclassified
“…Previous work (29) in piglet and rat enterocytes showed that ARG and bovine serum concentrate were the best stimulators of cell migration. We also found in those studies that cycloheximide blocked this effect, implicating mRNA translation in this process (M. Rhoads and W. Chen, unpublished observations).…”
mentioning
confidence: 90%
“…We used intestinal monolayer wounding with a razor blade, as described by McCormack et al (23) to determine whether amino acids stimulate intestinal cell migration, as previously described (29). Cdx2 cells were plated in six-well plates.…”
Section: Migration Assaymentioning
confidence: 99%
See 1 more Smart Citation